Prophylactic ECMO Support during Elective Coronary Percutaneous Interventions in High-Risk Patients: A Single-Center Experience. (4th February 2023) - Ungureanu, Claudiu; Blaimont, Marc; Trine, Hugues; Henin, Pierre; Courcelle, Romain; Laurent, Yves; Van Ruyssevelt, Patrick; Lepièce, Caroline; Huberlant, Vincent
Abstract : Introduction . Evidence regarding the impact of prophylactic implantation of venoarterial extracorporeal membrane oxygenation (VA-ECMO) for elective high-risk percutaneous coronary intervention (PCI) is limited. The purpose of this paper is to evaluate the outcome during index hospitalization and 3 years after interventions. Methods . This is an observational retrospective study including all patients undergoing elective, high-risk PCI and receiving VA-ECMO for cardiopulmonary support. Primary endpoints were in-hospital and 3- year major adverse cardiovascular and cerebrovascular event (MACCE) rates. Secondary endpoints were vascular complications, bleeding, and procedural success. Results . Nine patients were included in total. All patients were considered inoperable by the local heart team, and 1 patient had a previous coronary artery bypass graft (CABG). All patients were hospitalized for an acute heart failure episode 30 days before the index procedure. Severe left ventricular dysfunction was present in 8 patients. The main target vessel was the left main coronary artery in 5 cases. Complex PCI techniques were used: bifurcations with 2 stents in 8 patients, rotational atherectomy was performed in 3, and coronary lithoplasty in 1 case. PCI was successful in all of the patients with revascularization of all target and additional lesions. Eight of the 9 patients survived for at least 30 days after the procedure, and 7 patients survived for 3 years after the procedure. Regarding the complication rate, 2 patients suffered from limb ischemia and were treated by an antegrade perfusion, 1 patient had a femoral perforation that needed surgical repair, 6 patients had a hematoma, 5 patients had a significant drop in hemoglobin of more than 2 g/dl and received blood transfusions, 2 patients were treated for septicemia, and 2 patients needed hemodialysis. Conclusions . Prophylactic use of VA-ECMO in elective patients is an acceptable strategy for revascularization by high-risk coronary percutaneous interventions with good long-term outcomes for patients considered inoperable when a clear clinical benefit is expected. Regarding the potential risk of complications due to a VA-ECMO system, the selection of candidates in our series was based on a multiparameter analysis. The two main triggers in favor of prophylactic VA-ECMO in our studies were the presence of a recent heart failure episode and the high probability of periprocedural prolonged impairment of the coronary flow through the major epicardial artery.